Membuat Komunikasi Efektif Dalam Ekonomi Bisnis dan Kehidupan Sosial - Dita Ayu Susmita; Asrina Hasibuan; Suhairi Suhairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Communication is a very important thing in life, if we are not careful in communicating, it cannot be denied that it will be trigger misunderstandings. Communication in everyday life both in economic and social activities, not only by using verbal words, but also using non-verbal words. Without communication, there will be no interaction between humans. The interaction as a result of this communication is related to the attitude or behavior of each individual which must also be adjusted and/or to adapt to the various cultures of each. This culture will shape, strengthen and change attitudes and behavior both individually and socially in the cultural environment concerned. For that we must communicate well in order to create a good life between us. And also in communicating not only to convey messages, but to change behavior. Do not let what we convey, not in harmony with the behavior of the speaker. So that makes the communicant distrust and no longer want to communicate with us. So the existence of the communication management makes the implementation of the communication run effectivel, so that the messages or result expected from the delivery of the information is as expected. Management and communication presents an effective management and delivery scheme of information messages, so as to create harmony in the communication carried out.